Various Type Predation Freshwater Fish of The Larva aedes aegypti As a Control Method of Vector Biology Dengue Haemorrhagic Fever - Arif Widyanto; Sujoto Hernady; Sugeng Abdullah (Poltekkes Kemenkes Semarang, 2013)
The method used is an experiment in the laboratory with research design post test only design. The research was done by placing the unit into the fish samples in each experiment container,and fish fed with mosquito larvae A.aegypti continuously for up to 24 hours. The ability of fish to eat mosquito larvae were recorded and calcuteds the power of fish predation. The results showed that Beta splendens ability to prey on the larvae of Aedes aegypti is 278 larvae/24 hours, Carassius auratus is 201 larvae/24 hours, Poecelia reticulatta is 112 larvae/24 hours, Osteochilus vittatus is 78 larvae/24 hours and Trichogaster trichopterus is 188 larvae/24 hours. Most fish prey on the larvae of Aedes aegypti is Beta splendens that is an average of 278 larvae/24 hours, while the little fish is Osteochilus vittatus that is an average of as much as 78 larvae/24 hours.